The time of singing by male Capercaillies Tetrao urogallus at leks. Issue 1 (2nd January 2021) - Summers, Ron; Doubleday, Molly; Ames, Ellie
ABSTRACT: Counts at 16 Capercaillie leks revealed that singing started two hours before sunrise and reached a peak in the number that sang about one hour before sunrise. Most song had finished by sunrise, but some extended up to five hours after sunrise. The period of song was longer at leks where more males were seen and/or heard. Such field observations may be useful in interpreting data from unattended acoustic recorders.